2013
DOI: 10.1123/mcj.17.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Phase Entrainment Strength Scales With Movement Amplitude Disparity

Abstract: In the current study, we examined whether coupling influences resulting from unintended afference-based phase entrainment are affected by movement amplitude as such or by the amplitude relation between the limbs. We assessed entrainment strength by studying how passive movements of the contralateral hand influenced unimanual coordination with a metronome. Results showed that amplitude as such did not affect entrainment strength, whereas the amplitude relation between the hands did. Larger amplitudes of the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…abnormal unintended interlimb coupling. This interpretation is supported by observations that, for healthy participants, asymmetry in movement amplitude results in less pronounced unintended entrainment between the hands (Peper et al, 2008;Buchanan and Ryu, 2012;de Boer et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…abnormal unintended interlimb coupling. This interpretation is supported by observations that, for healthy participants, asymmetry in movement amplitude results in less pronounced unintended entrainment between the hands (Peper et al, 2008;Buchanan and Ryu, 2012;de Boer et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…B were thus likely due to the asymmetry in movement amplitude between the hands rather than abnormal unintended interlimb coupling. This interpretation is supported by observations that, for healthy participants, asymmetry in movement amplitude results in less pronounced unintended entrainment between the hands (Peper et al., ; Buchanan and Ryu, ; de Boer et al., ). Although the potential role of unintended coupling based on efferent signals was not explicitly addressed in this study, it is noteworthy that the stability of active bimanual coordination in CRPS patients was more reduced for in‐phase than for antiphase coordination.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For the vast majority of previous studies this cannot be verified because the performed amplitudes were neither reported nor considered in interpreting the results, which may have introduced potentially unjustified and confounded conclusions regarding coordinative stability as a function of movement frequency. Previous studies have indeed found indications that moving with larger amplitudes relates to enhanced interlimb [19][20][21][22][23][24][25][26] and perceptuo-motor coupling [27][28][29]. With the current study, we opt for a re-appraisal of the role of amplitude on coordinative stability (as was done for the first time two decades ago by, e.g., [16,19,20]) by presenting results of a refined, artifact-free analysis of the experimental data of Post, Peper, and Beek [21].…”
Section: Introductionmentioning
confidence: 99%